Corporate cash holdings: Evidence from a different institutional setting - Wolfgang Dobetz; Matthias C. Grüninger (University of Basel, Center of Business and Economics (WWZ), 2006)
This paper investigates the determinants of Swiss non-financial firms' cash holdings over the 1995 to 2004 period. The median Swiss firm holds almost twice as much cash and cash equivalents as the median UK or US firm. Our results indicate that there is a negative relationship between asset tangibility and cash holdings and a non-linear relationship between leverage and cash holdings. Dividend payments are positively related to cash reserves. However, there is no robust impact of firm size on cash. We also cannot detect a significantly positive relationship between growth opportunities (measured by the marketto- book ratio) and cash holdings, suggesting that the financing hierarchy theory is of little importance for the liquidity planning of Swiss firms. Dynamic panel estimation reveals that Swiss firms adjust their cash holdings only slowly towards an endogenous target cash ratio. Looking at a firm's corporate governance structure, we reveal a non-linear relationship between managerial ownership and cash holdings, indicating an incentive alignment effect and an opposing effect related to increasing risk aversion. Finally, our results indicate that firms where the CEO at the same time serves as the COB hold significantly more cash.
Keywords: G32; 330; Cash holdings; corporate governance; dynamic adjustment